Predicting Borderline Personality Disorder Symptoms Based on Childhood Trauma and Alexithymia With the Mediating Role of Mentalization in University Students - Shirazi, Zahra; Fazilati, Mansooreh (Mental Health and Lifestyle Journal, 2025)
The present study aimed to predict borderline personality disorder (BPD) based on childhood trauma and alexithymia, with the mediating role of mentalization in university students. This study employed a descriptive correlational design. The statistical population included male and female students from three branches of the Islamic Azad University: Tehran Central (Sardar Soleimani Complex, Faculty of Psychology and Educational Sciences), Tehran West (Payambar Azam Complex, Faculty of Architecture and Art), and Shahre Qods (Faculty of Engineering). These branches were selected from among all branches of the Islamic Azad University in Tehran during the 2024–2025 academic year. The sample size was determined to be 300 participants based on the method proposed by Kline (1990), and they were selected through a non-random convenience sampling method. Data were collected using the Jackson and Claridge Borderline Personality Scale (1991), the Childhood Trauma Questionnaire by Bernstein and Fink (2003), the Toronto Alexithymia Scale (1985), and the Mentalization Scale by Fonagy et al. (2016). Statistical analyses were performed using SPSS version 28 and AMOS version 24. The results of data analysis showed that childhood trauma had a standardized coefficient of 0.175 on borderline personality disorder and the direction of the effect was positive. Additionally, alexithymia had a standardized coefficient of 0.334 on borderline personality disorder and the direction of the effect was positive. Furthermore, childhood trauma had no significant effect on borderline personality disorder through the mediating role of mentalization (p = 0.358). However, alexithymia had a significant effect on borderline personality disorder through the mediating role of mentalization (p = 0.016). Finally, the empirical model demonstrated acceptable and appropriate fit, and the overall model was confirmed. Childhood trauma and alexithymia play important roles in the emergence of borderline personality disorder symptoms, and mentalization served as a mediator only in the relationship between alexithymia and borderline personality disorder. These findings highlight the necessity of incorporating emotion regulation training and strengthening mentalization skills in preventive and therapeutic interventions.